Pengaruh Good Corporate Governance Terhadap Kualitas Laba Perusahaan Sub Sektor Pertambangan Logam dan Mineral - Ilham, Rico Nur; Putri, Debi Eka; Putra, Hendrick Sasimtan; Sari, Eka Purnama; Siallagan, Shintauli (Jurnal Ilmu Manajemen, 2022)
The purpose of this research is to determine the effect of good corporate governance on earnings quality both simultaneously or partially. This research was conducted using quantitative descriptive analysis. The population in this study is all companies that are included in the research object, using purposive sampling, obtained by 6 companies during 5 years of research that can be used as a sample so that the number of observations is as much as 30. Analysis technique: classical assumption test, multiple linear regression analysis, correlation coefficient, coefficient of determination, and hypotesis testing. The results of simultaneously  Good corporate governance have a positive and insignificant effect on earnings quality.  The results partially: Institutional ownership and independent commissioners have a negative and insignificant effect on earnings quality, but public ownership and audit committees have a positive and significant effect on earnings qualit in Metals and Mineral Sub Sector Companies Listed on the Indonesia Stock Exchange.